EVALUASI PERKERASAN JALAN KAKU (RIGID PAVEMENT) PADA JALAN SM RAJA MEDAN DENGAN METODE BINA MARGA - Sidabutar, Ros Anita; Saragi, Yetty Riris; Pasaribu, Humisar; Pardede, Maruli; Hutabarat, Torang (Jurnal Visi Eksakta, 2021)
axle vehicles with the aim of shortening the distance and travel time from one place to another, as well as an infrastruture that is needed to support development. The design of the Sisingamangaraja – Lubuk Pakam road pavement consisting of a cement concrete slab as a foundation layer and a foundation laver above the subgrade. The purpose of this study was to evaluate the thickness of the pavement using the Highways Method. The research method used is the secondary data collection method. The data collected include traffic data, concrete data, soil data, vehicle axle free data, CBR modulus of subgrade. Plaanning the thickness of the road pavement concrete slab using the Highways Method obtained 300 mm. A planner is expected to have “felling engineering” supported by extensice knowledge and experience gained in the field.